Evaluation of ground grain sorghum as an alternative to dry-rolled corn in finishing steer diets - Johnson, Harleigh Ann (My University, 2025)
Interest in the ability of grain sorghum production to conserve water by reduced crop irrigation compared to corn, while also meeting nutritional demands of the feedlot industry has motivated the following evaluations. One finishing cattle study and a complementary in vitro experiment were conducted to evaluate use of ground grain sorghum as an alternative to dry-rolled corn in finishing steer diets. The finishing cattle study was conducted to evaluate feedlot performance and carcass characteristics, utilizing yearling steers (n=300; 346 ± 11 kg initial body weight). Cattle were allocated randomly to feedlot pens (30 pens; 10 steers/pen), and pens were assigned randomly to dietary treatments within blocks (15 blocks). Steers were fed once daily and feed amounts were allocated to result in only traces of feed remaining in the bunk the following day. Fresh fecal pats were collected from pen surfaces on day 120 and analyzed for concentrations of acid insoluble ash, starch, and organic matter to estimate diet digestibility. Steers were harvested after 182 d on feed and carcass data were collected after 96 h of refrigeration. Muscle tissue samples from the infraspinatus and semitendinosus muscles were collected from a subset of 32 carcasses to be analyzed for concentrations of fatty acid methyl esters. Corn and sorghum diets yielded similar digestibilities (P > 0.10) of organic matter (79.0 vs 78.3%, SEM=2.29) and starch (91.4% vs 88.5%, SEM=1.85). Cattle fed corn consumed less DM but had greater ADG and G:F compared to those fed sorghum (DM intake: 10.93 vs 11.54 kg/d; ADG: 1.61 vs 1.46 kg/d; G:F: 0.1533 vs 0.1327; P < 0.01). Calculated NEm (2.24 vs 2.08 Mcal/kg) and NEg (1.55 vs 1.42 Mcal/kg) were greater for corn compared to sorghum (P < 0.03). Heavier carcasses with greater marbling and superior quality grades were observed for cattle fed corn produced compared to those fed sorghum, resulting in $112 greater carcass value for cattle fed corn (P < 0.01). Meat tissues from corn-fed steers were characterized by greater concentration of total fatty acids (FA) and monounsaturated FA, specifically in the infraspinatus (P < 0.05). Meat tissues from grain sorghum-fed steers contained greater polyunsaturated FA (PUFA) proportion in the semitendinosus (P < 0.01). In the second experiment, in vitro fermentation characteristics including cumulative gas production, volatile fatty acid (VFA) profiles, and in vitro dry matter disappearance of grain sorghum and corn for beef steers were evaluated. A randomized complete block design was utilized to evaluate three grain sorghum and three corn samples (hybrids unknown) from the feedlot study. Compared to sorghum, IVDMD tended to be greater for corn (59.18% vs 62.31%; P = 0.07), but concentrations of VFAs were not different (P < 0.01). Cultures with grain sorghum as substrate produced less gas compared to those containing corn as substrate (P < 0.01), but rates of gas production did not differ (P > 0.10). These results indicate that when compared to diets containing dry-rolled corn, diets containing ground grain sorghum are inferior. diets cause feedlot steers to underperform and produce inferior carcasses.
Keywords: Feedlot; Milo; Digestibility; Performance